2006
DOI: 10.1093/jxb/erl140
|View full text |Cite
|
Sign up to set email alerts
|

Effect of activase level and isoform on the thermotolerance of photosynthesis in Arabidopsis

Abstract: Ribulose 1,5-bisphosphate carboxylase/oxygenase (Rubisco) activation decreases under moderate heat stress. This decrease is caused by an impairment of activase function, which is exacerbated by faster rates of Rubisco deactivation at elevated temperatures. To determine if stromal oxidation causes inhibition of activase, transgenic Arabidopsis plants expressing suboptimal amounts of either the redox-regulated 46 kDa alpha- or non-redox regulated 43 kDa beta-isoform of activase were examined. Photosynthesis, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 43 publications
2
35
0
Order By: Relevance
“…Rubisco activase is a nuclear-encoded stromal protein present under two forms with different properties (Salvucci et al, 2006;Portis et al, 2008;Carmo-Silva and Salvucci, 2016).The longer redoxregulated α-isoform and the shorter β-isoform of rubisco activase are in some plants encoded in the same gene and are synthesized on two mRNAs produced from the same pre-mRNA by alternative splicing as illustrated in Fig. 3, process 2b (Werneke et al, 1989;Salvucci et al, 2003).…”
Section: Impacts On Rubisco and Rubisco Activasementioning
confidence: 99%
“…Rubisco activase is a nuclear-encoded stromal protein present under two forms with different properties (Salvucci et al, 2006;Portis et al, 2008;Carmo-Silva and Salvucci, 2016).The longer redoxregulated α-isoform and the shorter β-isoform of rubisco activase are in some plants encoded in the same gene and are synthesized on two mRNAs produced from the same pre-mRNA by alternative splicing as illustrated in Fig. 3, process 2b (Werneke et al, 1989;Salvucci et al, 2003).…”
Section: Impacts On Rubisco and Rubisco Activasementioning
confidence: 99%
“…The slightly larger form contains two cysteine residues in the C-terminal extension allowing a redox regulation via the thioredoxin system (Portis et al, 2008). The heat sensitivity of photosynthesis was found to be due to thermal denaturation of Rubisco activase and not to the oxidation of the cysteine residues in the larger form (Salvucci et al, 2006). The complex regulation of Rubisco activase (and as a consequence of Rubisco) and CO 2 fixation is not yet fully explored for all major crop plants and will remain a subject of research during the next years.…”
Section: Rubisco Activasementioning
confidence: 98%
“…It should also be important to delineate various cellular events that may be affected by the aberrations caused in protein metabolism. Salvucci et al (2006) recently showed that thermal denaturation of rubisco activase is one of the key factors responsible for loss of rubisco activation under heat stress. According to Sage and Kubien (2007), limitations in electron transport and rubisco activase capacity should be more common, in the warmer, high CO 2 conditions expected by the end of the century.…”
Section: Synthesis To Propose a Modelmentioning
confidence: 99%